تێڕامانێک لەسەر ڕۆمانى سەگوەڕ - محەمەد, عەبدولقادر حەمەئەمین (Sulaimani Journal for Humanities, 2003)
Our study, entitled "contemplating the novel "dog barking" has taken a direction, in terms of reading and evaluation that breaks up all the traditional and dogmatic principles from which kurdish Novel has been suffering. Since the kurdish Novel has turned into a maintainer of traditional essence, ideal sanctification and ideological conflicts, therefore. 1- It should be read with humanistic contemporary mentality, its secrets and universal implication as the novel itself comes simultaneous with the rise of modernity. It also represents a complete presence of the intellectual and philosophical dimensions which are in line with the writer's ideal conception of life, humanity and existence. 2- The writer's internal potential consists in the fact that he has got rid of the absolute ideological and totalitarian system prevalent in the kurdish society. He has produced a free flow of a reactivation process of the kurdish individual who is in conflict with the metaphysics. 3- Time and events, time shapes up outside the time of the novel which is not in line with the historical reality of a novel or the social life of (1). This is because events mostly take place in accordance with the narrator's psychological state. The time , however, is not subjected to traditional frameworks as the events make sudden appearances, they are not compatible with realities. The "present" tense is employed which is cut off from the time sequences. 4- characters & narrator: The narrator is not in control and doesn't provide us with information about the characters. This is because there is no pivotal character to become the center for the rest of the characters. The narration, however, has gone out of the traditional form and is not unified in displaying the events. 5- The novel, in general, represents confusion in many times & places. Time is an object of question and an element of solution.